As doping of Si–Ge–Sn epitaxial semiconductor materials on a commercial CVD reactor. (17th August 2017) - Bhargava, Nupur; Margetis, Joe; Tolle, John
Abstract: In this work we present the As doping, via AsH3, of Ge1− x Sn x and Siy Ge1− y − x Sn x alloys grown in a commercial RPCVD reactor. The composition, thickness, and resistivity of the layers were measured for varying AsH3 flows and AsH3 growth kinetics was discussed. We find that the addition of As to the lattice induces compressive strain in the layer despite a smaller covalent radius relative to Ge and Sn. N -type dopant incorporation and activation is compared for AsH3 and PH3 -based processes, and we find that As incorporates more efficiently than P. As concentrations > 2 × 10 20 cm −3 were achieved for both Ge1− x Sn x and Siy Ge1− y − x Sn x with resistivity as low as 0.6 mΩ cm.